Ionizing Radiation in Undergraduate Physics curricula: An analysis of Basil Bernstein’s pedagogic device - Delarco Bertoni, Eric; Londero, Leandro (Revista de Estudios y Experiencias en Educación, 2024)
We present the results of a research analysis on the inclusion of ionizing radiation as a teaching subject in undergraduate Physics curricula in São Paulo State, after the new National Curriculum Guidelines for Initial Training of Basic Education Teachers came into force. For this purpose, we identified Physics undergraduate programs using the Brazilian Federal Government’s e-MEC platform and retrieved their Curricular/Pedagogic Political Projects, syllabi and course catalog by accessing the respective websites. Based on Basil Bernstein’s theory of the pedagogic device, especially the concepts of Official Recontextualizing Field (ORF) and Pedagogic Recontextualizing Field (PRF), we analyze the way in which the new educational policies influenced the curricula of the programs investigated. Although ORF documents state the importance of including ionizing radiation in the PRF, only three (12% of the total of 25) programs offer a specific course on the topic. Given this scenario, the curricula should be updated to include ionizing radiation teaching in initial teacher education programs and ensure it is adequately addressed by providing times, spaces and teaching methodologies focused on the teaching-learning processes of this topic, allowing future teachers to recontextualize this subject in Basic Education.